Phytochemical analysis and anti-inflammatory activity of wild Yam Dioscorea Hispida Dennst - Mohamad, Norfarha Shahera (2018)
Dioscorea hispida Dennst which belongs to Dioscoreaceace family is a valuable source of many useful phytochemical compounds in it. D. hispida is wild yam that has medicinal properties due to its chemical contents that can be used for drug development. D. hispida contains of high steroids in the form of saponins. The aim of this research is to analyze the phytochemical content present in D. hispida which were Flavonoids, Steroids, Saponins, Tannins, Alkaloids, Phenolics, Glycosides and Terpenoids. In this study, the tuber of D. hispida was used and prepared with three different polarity solvents which were ethanol, hexane and water. Besides, the anti-inflammatory activity of D. hispida also had been determined by using in-vitro method of denaturation inhibition of protein in plants. The active chemical compounds of D. hispida also had been measured using Gas Chromatoghraphy-Mass Spectrometry (GCMS). As a result, D. hispida was been identified to have all of the chemical tested which were Flavonoids, Steroids, Saponins, Tannins, Alkaloids, Phenolics, Glycosides and Terpenoids. Next, the denaturation inhibition of proteins of water extracts recorded highest percentage than other extracts thus supporting the facts that D. hispida possess anti-inflammatory activity. GC-MS analysis also showed that there were seven bioactive compounds showing and had potential of many biological activities for both ethanol extracts and hexane extracts. From this research, it is expected and recommended that the phytochemical analysis of D. hispida can be used in discovering new research especially in medicinal industry such as drug development.